Gum Arabic and breast cancer biology: Biotechnology perspective - Elnour, Ahmed Adam Hassan Mohammed (Springer Nature, 2025)
This book delves into the intersection of gum arabic, a natural product derived from Acacia gums (AGs) including Acacia sengal, Acacia seyal and Acacia polyacantha gum, and breast cancer (BC)biology from a biotechnology perspective. It explores the history, extraction, characterization, and biological applications of secondary metabolites (SMs) extracted from AGs. The chapters cover topics such as the physicochemical properties of AGs, advanced extraction methods for secondary metabolites, and their diverse biological applications, including antimicrobial, anti-inflammatory, and anticancer properties. The book also examines state-of-the-art breast cancer research, its impact on sustainable development goals, and the potential applications of AG's secondary metabolites in BC cell lines. Additionally, it discusses the opportunity to transfer cancer-on-a-chip technology to Islamic Development Bank member countries (IsDB-MCs) and explores the application of breast-on-a-chip technology using AGs-secondary metabolites (SME). This comprehensive book combines the fields of biotechnology, breast cancer biology, and natural product research, offering a unique perspective on the potential role of gum Arabic or AGs secondary metabolites in breast cancer research and treatment. Researchers in the fields of biotechnology, oncology, and natural product chemistry find this book invaluable. Whether you are exploring new frontiers in cancer treatment or a practitioner seeking novel therapeutic approaches, this book provides critical insights into innovative strategies for combating breast cancer. Additionally, it serves as an essential resource for policymakers interested in integrating development goals with healthcare advancements.